Child’s right to life in the light of the objectives of Islamic Law (Maqasid al-Shari’ah) - Mohd, Azizah; Alhaji, Umar Alkali (2015)
Right to Life is one of the Fundamental Rights that is guaranteed to all including children. This right is recognized by all legal systems in the world nationally and internationally. Many scholarly writings also pronounced the value of children’s rights in many perspectives. Currently, Children’s right to life is simply violated by some in order to preserve their own personal interest. Islamic law (the Shari’ah) regards that right to life is one of the most essential values that deserves protection, the neglect of which will result to destruction and disorder in the society. Therefore, under Islamic law, protection of child’s right to life becomes one of the most important objectives of the Shari’ah. This paper seeks to research the underlying principle behind protection of life in Islam in particular child’s right to life. The research focuses on examining the Child’s right to life in the light of the objectives of Islamic law (Maqasid al-Shari’ah). Discussion includes examination on means and ways of protection that guarantee protection of child’s right to life in Islam. The research will mainly employ library research. Primary references will be the Quran and the Sunnah of the Prophet (pbuh) as they serve as primary sources of Islamic law. Other references will include primary and contemporary works and writings of Muslim scholars on protection of children’s rights to life in Islam. It is hoped that the findings of this research will provide additional resources on protection of children’s rights beneficial to all legal practitioners, academics, students, researchers and public at large.